A sensitive probe for amyloid fibril detection with strong fluorescence and early response. Issue 29 (27th April 2018) - Zheng, Xiaolin; Xu, Zhenzhen; Li, Haiyang; Fu, Hongbing
Abstract : We synthesized a new probe, 4-[2-(2-naphthyl)-( E )-ethenyl]-benzyl(triphenyl)phosphonium bromide (NEB), to detect the formation of amyloid fibrils of bovine insulin. Abstract : We synthesized a new probe, 4-[2-(2-naphthyl)-( E )-ethenyl]-benzyl(triphenyl)phosphonium bromide (NEB), to detect the formation of amyloid fibrils of bovine insulin. The fluorescence intensity of NEB in the presence of insulin fibrils was 30 times higher than that before fibrillation, with the fluorescence quantum yield increased from 2.5% to 78%. In comparison with the commercially available probe, thioflavin T (ThT), NEB exhibits a 10 times stronger fluorescence and a shorter identification lag phase for detecting insulin fibrillation, indicating a higher sensitivity in detection of insulin oligomers and fibrils.